Implementasi Keterbukaan Informasi Publik Pemerintah Kabupaten Mukomuko, Provinsi Bengkulu - Yuono, Cipto (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The implementation of public information disclosure in Mukomuko Regency through the Office of Communication and Informatics has been running through the formation of PPID Mukomuko in 2014, but the legal regulations were only formed after the Office of Communication and Informatics was established in January 2017. The purpose of this research is to find out why the Communication and Informatics Office implements public information disclosure and to find out how the implementation process of public information disclosure in Mukomuko Regency is carried out. This research uses a kaulitative approach and case study method, collecting data through observation, interviews and documentation. The results showed that the Mukomuko District Government has implemented the dissemination of public information transparently to the public to date, through the establishment of PPID devices (Information Management and Documentation Officers) and routinely conducting evaluations every year.